Understanding COVID-19 in Nepal - Pun, Sher Bahadur; Mandal, Shrawan; Bhandari, Lilanath; Jha, Santoshananda; Rajbhandari, Sagar; Mishra, Abdhesh Kumar; Sharma Chalise, Bimal; Shah, Rajesh (Journal of Nepal Health Research Council, 2020)
The novel coronavirus COVID-19 (SARS-CoV-2) was first reported on 31 December 2019 in Wuhan City, China. The first case of COVID-19 was officially announced on 24 January, 2020, in Nepal. Nine COVID-19 cases have been reported in Nepal. We aim to describe our experiences of COVID-19 patients in Nepal. Keywords: COVID-19; experience; Nepal